2007
DOI: 10.1021/cm071462f
|View full text |Cite
|
Sign up to set email alerts
|

Template Effect of Chain-Type Polyamines on Pore Augmentation: Five Open-Framework Zinc Phosphates with 16-Ring Channels

Abstract: Five new zinc phosphates with differently unique 3D framework topologies, (H3dien)[Zn3(HPO4)3(PO4)] (1), (H2dien)1.5[Zn3(HPO4)3(PO4)] (2), (H3dien)[Zn3(H2PO4)(HPO4)(PO4)2] (3), (H3dien)[Zn3(HPO4)3(PO4)]·1.5H2O (4), and (H4tepa)0.5[Zn2.5(HPO4)2(PO4)]·1.5H2O (5), where dien = H2NC2H4NHC2H4NH2 and tepa = H2N(C2H4NH)3C2H4NH2, have been synthesized under mild hydrothermal or solvothermal conditions and characterized by single-crystal X-ray diffraction, thermal analysis, solid-state NMR, UV–vis, or photoluminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The literature abounds with report of many open-framework structured materials prepared using a variety of organic amines as structure-directing agents. ,, There have been some studies on the use of a single amine for preparing a number of different structures . Recently, Wang and co-workers have shown that it is possible to prepare different zinc phosphate phases using the organic amine DETA which has already been shown to give rise to three different zinc phosphate phases . In all these studies, there has been no correlation between the starting synthesis composition and the final solid product.…”
Section: Comment On the Synthesismentioning
confidence: 99%
“…The literature abounds with report of many open-framework structured materials prepared using a variety of organic amines as structure-directing agents. ,, There have been some studies on the use of a single amine for preparing a number of different structures . Recently, Wang and co-workers have shown that it is possible to prepare different zinc phosphate phases using the organic amine DETA which has already been shown to give rise to three different zinc phosphate phases . In all these studies, there has been no correlation between the starting synthesis composition and the final solid product.…”
Section: Comment On the Synthesismentioning
confidence: 99%
“…It has once been reported that a ZnPO 4 with the same structure of CoZnPO 4 -V was obtained previously. However, the quality of the crystals of this ZnPO 4 was always too poor to give better refinement results [5] . In our research, both the zinc-cobalt composition in the framework and the presence of small amines as the assistant organics play a key role in the growth of the perfect crystal.…”
Section: The Preparation Of the Perfect Large Single Crystal Of Coznpmentioning
confidence: 99%
“…Among the increasingly synthesized frameworks, the system of metal phosphates and phosphites has shown a greater disposition to form extra-large-pore structures [5][6][7][8] . Up to now, almost all the largest channel (including 24-ring and 26-ring) frameworks have been obtained in phosphates and phosphites [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Zincophosphates are an important subset of the large phosphate family. Although over 20 different zincophosphates with various structural dimensionalities and stoichiometries have been synthesized and characterized, the preparation of zinc phosphates with novel structures is still possible. Most of these structures are built up from vertex-linked ZnO 4 and PO 4 tetrahedra, and connectivity between two or more ZnO 4 tetrahedra through Zn−O−Zn linkages is rare . These materials are typically synthesized hydrothermally using a zinc salt and phosphoric acid, together with an organic amine acting as a template or structure-directing agent.…”
mentioning
confidence: 99%